A Monte Carlo Simulation Approach for Beta‐Lactam Dosing in Critically Ill Patients Receiving Prolonged Intermittent Renal Replacement Therapy. (10th May 2018) - Jang, Soo Min; Gharibian, Katherine N.; Lewis, Susan J.; Fissell, William H.; Tolwani, Ashita J.; Mueller, Bruce A.
Abstract: Cefepime, ceftazidime, and piperacillin/tazobactam are commonly used beta‐lactam antibiotics in the critical care setting. For critically ill patients receiving prolonged intermittent renal replacement therapy (PIRRT), limited pharmacokinetic data are available to inform clinicians on the dosing of these agents. Monte Carlo simulations (MCS) can be used to guide drug dosing when pharmacokinetic trials are not feasible. For each antibiotic, MCS using previously published pharmacokinetic data derived from critically ill patients was used to evaluate multiple dosing regimens in 4 different prolonged intermittent renal replacement therapy effluent rates and prolonged intermittent renal replacement therapy duration combinations (4 L/h × 10 hours or 5 L/h × 8 hours in hemodialysis and hemofiltration modes). Antibiotic regimens were also modeled depending on whether drugs were administered during or well before prolonged intermittent renal replacement therapy therapy commenced. The probability of target attainment (PTA) was calculated using each antibiotic's pharmacodynamic target during the first 48 hours of therapy. Optimal doses were defined as the smallest daily dose achieving ≥90% probability of target attainment in all prolonged intermittent renal replacement therapy effluent and duration combinations. Cefepime 1 g every 6 hours following a 2 g loading dose, ceftazidime 2 g every 12 hours, and piperacillin/tazobactam 4.5 g every 6 hours attained the desired pharmacodynamic target in ≥90% of modeled prolonged intermittent renal replacement therapy patients. Alternatively, if an every 6‐hours cefepime regimen is not desired, the cefepime 2 g pre‐prolonged intermittent renal replacement therapy and 3 g post‐prolonged intermittent renal replacement therapy regimen also met targets. For ceftazidime, 1 g every 6 hours or 3 g continuous infusion following a 2 g loading dose also met targets. These recommended doses provide simple regimens that are likely to achieve the pharmacodynamics target while yielding the least overall drug exposure, which should result in lower toxicity rates. These findings should be validated in the clinical setting.